Legal Urgency Regarding Efforts To Regain Rights To Land Taken From The Government Based On The Basic Agrarian Law - Anak Agung Kompiang Gede; Faisal Santiago (Pusat Riset dan Inovasi Nasional, 2025)
. This study examines the role of the state in managing land as a natural resource controlled by the state, by the mandate of Article 33 Paragraph (3) of the 1945 Constitution and Article 2 Paragraph (2) of the UUPA, which emphasizes the use of land for the prosperity of the people. Through the social function of land contained in Article 6 of the UUPA, land is viewed as the right of individuals or legal entities and must benefit the wider community. The land reclamation process, as one of the state's efforts to return or transfer control of misused land, is key to ensuring fair and sustainable management. This study also highlights the importance of state authority in regulating the use and distribution of land to prevent monopolies and maintain public welfare through agrarian policies that favor the public interest.